Simple flow-injection system for the simultaneous determination of nitrite and nitrate in water samples - Burakham R. (2014)
A novel spectrophotometric reaction system was developed for the determination of nitrite as well as nitrate in water samples, and was applied to a flow-injection analysis (FIA). The spectrophotometric flow-injection system coupled with a copperised cadmium reductor column was proposed. The detection was based on the nitrosation reaction between nitrite ion and phloroglucinol (1,3,5-trihydroxybenzene), a commercially available phenolic compound. Sample injected into a carrier stream was split into two streams at the Y-shaped connector. One of the streams merged directly and reacted with the reagent stream: nitrite ion in the samples was detected. The other stream was passed through the copperised cadmium reductor column, where the reduction of nitrate to nitrite occurred, and the sample zone was then mixed with the reagent stream and passed through the detector: the sum of nitrate and nitrite was detected. The optimised conditions allow a linear calibration range of 0.03-0.30mug NO(2)(-)-Nml(-1) and 0.10-1.00mug NO(3)(-)-Nml(-1). The detection limits for nitrite and nitrate, defined as three times the standard deviation of measured blanks are 2.9ng NO(2)(-)-Nml(-1) and 2.3ng NO(3)(-)-Nml(-1), respectively. Up to 20 samples can be analyzed per hour with a relative standard deviation of less than 1.5%. The proposed method could be applied successfully to the simultaneous determination of nitrite and nitrate in water samples.